FINANCIAL DISTRESS DI BUMN INDONESIA DAN FAKTOR-FAKTOR YANG MEMPENGARUHI INVESTASI, LEVERAGE DAN CASH FLOW OPERATION TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN BUMN - Aries Widya Gunawan; Aminullah Assagaf; Nur Sayidah; Alvy Mulyaningtyas (EKUITAS (Jurnal Ekonomi dan Keuangan), 2019)
This study aims to analyze the effect of managerial compensation, working capital, investment growth, and cash flow operations on financial distress in state-owned companies. This study uses several independent variables that empirically affect operating cash flow that has an impact on SOE financial distress. This study also uses financial indicators as control variables to limit the influence of factors or other variables outside the independent variable. The control variable used in this study is leverage. The researcher selected secondary data from 2014-2017 from a sample of 19 State-owned enterprises that received subsidies or equity participation from the government. The analytical method used is a statistical approach through the classical assumption test and linear regression model. The results of this study indicate that Working Capital and leverage have an influence on Financial Distress. Management Compensation, Investment Growth, and Cash Flow Operations have no influence on Financial Distress.